PENGEMBANGAN APLIKASI ABHIDHAMMA V.1.0 BERBASIS ANDROID - TRI SUYATNO (Al-Fikru : Jurnal Pendidikan Dan Sains, 2023)
The purpose of this research is to develop existing teaching materials (powerpoint) into Android-based teaching materials. Which is in the form of an application (apk) that is integrated with a personal smartphone. This application is expected to facilitate the teaching and learning process. This research uses the research and development (R&D) method, which is a research method used to produce certain products, and test the effectiveness of these products.Based on the results of the questionnaire for carrying out the media test. Based on the results of the media test, the following results were obtained, the result was 92% and had very good criteria and there was no need to revise the media being developed. Meanwhile, a questionnaire was given to material experts. The researcher got the data from filling out the 80% criterion questionnaire and had good criteria. With the development of Android-based learning media, it is hoped that it will facilitate learning in the Abhidhamma Pitaka course at STAB Negeri Raden Wijaya. In addition, the media can be used as teaching materials which can be optimized as a second source after the Abhidhamma book.Keywords: Abhidhamma, Android, Learning Media, Applications